Highly sensitive multicolor uncooled photoresponse and imaging based on symmetry breaking heterojunction - Liuping Liu; Sheng Ni; Fengyi Zhu; Yuling Zhu; Changlong Liu; Xutao Zhang; He Zhu; Jiazhen Zhang; Donghai Zhang; Changyi Pan; Li Han; Weiwei Tang; et al. (InfoMat)
Abstract Multicolor photodetection, essential for applications in infrared imaging, environmental monitoring, and spectral analysis, is often limited by the narrow bandgaps of conventional materials, which struggle with speed, sensitivity, and room‐temperature operation. We address these issues with a multicolor uncooled photodetector based on an asymmetric Au/SnS/Gr vertical heterojunction with inversion‐symmetry breaking. This design utilizes the complementary bandgaps of SnS and graphene to enhance the efficiency of carriers' transport through consistently oriented built‐in electric fields, achieving significant advancements in directional photoresponse. The device demonstrates highly sensitive photoelectric detection performance, such as a responsivity (R) of 55.4–89.7 A W–1 with rapid response times of approximately 104 μs, and exceptional detectivity (D*) of 2.38 × 1010 Jones ~8.19 × 1013 Jones from visible (520 nm) to infrared (2000 nm) light, making it suitable for applications demanding an imaging resolution of ~0.5 mm. Additionally, the comparative analysis reveals that the asymmetric vertical heterojunction outperforms its counterparts, exhibiting approximately 9‐fold the photoresponse of symmetric vertical heterojunction and almost 100‐fold that of symmetric horizontal heterojunction. This highly sensitive multicolor detector holds significant promise for applications in advanced versatile object detection and imaging recognition systems.